Research progress on heat stress response mechanisms in Aspergillus niger - Pan, Yongtao; Li, Jun (Frontiers in Microbiology, 2026)
Aspergillus niger, an industrial filamentous fungus recognized as GRAS (Generally Recognized as Safe) and vital for food fermentation and enzyme production, has an optimal fermentation temperature around 30 °C; however, heat stress in industrial systems impairs its cellular viability and reduces target product synthesis efficiency. This review systematically summarizes the multi-level coordinated heat stress response mechanisms of A. niger by integrating existing research findings, revealing that the fungus copes with heat stress via cell membrane remodeling, rapid accumulation of compatible solutes, cAMP/PKA-mediated metabolic reprogramming, protein quality control, and activation of antioxidant defense systems. These mechanisms synergistically enhance A. niger’s heat resistance, while current research still lacks data on early stress signaling events, complete PKA downstream regulatory networks, and multi-omics integration. The review’s innovation lies in identifying potential adaptive strategies specific to eukaryotic filamentous fungi (e.g., non-classical membrane regulation) and providing a theoretical basis for improving A. niger’s thermotolerance through metabolic engineering.